Effect of Inorganic fertilizers and FYM on Growth, Yield and Quality Parameters of Onion in Lateritic Soils of Konkan - DODAKE, S. B.; THORAT , R.; DABAKE, D. J. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
.